Lobectomy vs. segmentectomy. A propensity score matched comparison of outcomes. Issue 5 (May 2019) - Roman, M.; Labbouz, S.; Valtzoglou, V.; Ciesla, A.; Hawari, M.; Addae-Boateng, E.; Thorpe, J.A.; Duffy, J.P.; Majewski, A.
Abstract: Background: Segmentectomy has emerged as a lung parenchymal sparring alternative to the gold standard lobectomy in non-small cell lung cancer (NSCLC) patients. We hypothesized that there is parity between functional, local recurrence and survival outcomes. Patients and methods: Parenchymal sparring procedures including anatomical segmentectomies were propensity score matched 1:1 with lobectomies (n = 64). The primary outcomes included survival, functional and oncological outcomes. The oncological outcomes were: post-operative histology, clear margins and local recurrence rates. Kaplan Meier survival curves were used to compare the survival. Oncological and functional variables were assessed by Fischer exact test and t -test. Results: The pre-operative performance status, ASA grade, lung function, risk factors, surgical approach and tumour histology were similar between the groups. The tumour size was significantly higher for lobectomies (32.4 ± 17 vs. 24.6 ± 12 mm, p = 0.01). The tumour staging in the segmentectomy group was similar to the lobectomy group (Ia; 50 vs. 34%; Ib: 29 vs. 37%; IIa 11 vs. 9.3%; IIb 5 vs. 14%; IIIa 5 vs. 4.6%, p = 0.83). The loco-regional recurrence was lower in the segmentectomy group (1.5 vs. 3.1%, p = 0.69). The up-staging and down-staging post-surgery was similar in both groups, while neo-adjuvant therapy was used in 5 lobectomy and 3 segmentectomy cases. The survival was similar at 1 year between the groups (88 vs. 92%, p = 0.65). Between 4 and 5 years, the survival reduced in the parenchymal sparing group to 39% vs. 68% in the lobectomy group (p = 0.04). Conclusion: Surgical selection bias could be an important confounder in the selection of patients undergoing segmentectomy. Similar up and down staging were demonstrated in the two groups. This is one of the first studies to investigate the results of segmentectomy versus lobectomy in stage II/IIIa NSCLC tumours. No significant differences were found in functional outcomes, but the survival decreased after 4 years in the segmentectomy group, which could be explained by lower survival in the stage II/IIIa tumours treated with segmentectomy.